Retention of Prey Genetic Material by the Kleptoplastidic Ciliate Strombidium cf. basimorphum - Maselli, Maira; Anestis, Konstantinos; Klemm, Kerstin; Hansen, Per Juel; John, Uwe (Frontiers in Microbiology, 2021)
Many marine ciliate species retain functional chloroplasts from their photosynthetic prey. In some species the functionality of the acquired plastids is connected to the simultaneous retention of prey nuclei. To date, this has never been documented in plastidic Strombidium species. The functionality of the sequestered chloroplasts in Strombidium species is thought to be independent from any nuclear control and only maintained via frequent replacement of chloroplasts from newly ingested prey. Chloroplasts sequestered from the cryptophyte prey Teleaulax amphioxeia have been shown to keep their functionality for several days in the ciliate Strombidium cf. basimorphum. To investigate the potential retention of prey genetic material in this ciliate we applied molecular marker specific for this cryptophyte prey. Here, we demonstrate that genetic material from prey nuclei, nucleomorphs and ribosomes is detectable inside the ciliate for at least five days after prey ingestion. Moreover, single-cell transcriptomic revealed the presence of transcripts of prey nuclear origin in the ciliate after four days of prey starvation. These new findings might lead to the reconsideration of the mechanisms regulating chloroplasts retention in Strombidium ciliates. The development and application of molecular tools appear promising to improve our understanding on chloroplasts retention in planktonic protists.